Early-life exposure to di (2-ethyl-hexyl) phthalate: Role in children with endocrine disorders - Zeng, Fa; Zhang, Luodan; Deng, Fang; Lou, Shuiping (Frontiers in Cell and Developmental Biology, 2023)
Abstract: Di (2-ethyl-hexyl) phthalate (DEHP), one of endocrine-disrupting chemicals (EDCs), has widespread concern due to its serious health hazards. Exposure to DEHP in the early stage of life affects fetal metabolic and endocrine function, which even would cause genetic lesions. To date, it is widely believed that the increasing incidence of childhood obesity and diabetes in adolescents is related to the impact of DEHP on glucose and lipid homeostasis in children. However, there remains a knowledge gap to recognize these adverse effects. Thus, in this review, besides the exposure routes and levels of DEHP, we further outline the effects of early-life exposure to DEHP on children and potential mechanisms, focusing on the aspect of metabolic and endocrine homeostasis.